PERANCANGAN INFOGRAFIK RUMAH-KITA ORGANISASI YAYASAN KASIH ANAK KANKER INDONESIA - Kelvin Aditya Prastyo (Jurnal Vicidi, 2020)
Child cancer is one of the biggest contributors to death in Indonesia and therefore the NOP organization, YKAKI, is there to help children with cancer get through existing diseases. YKAKI is a well-known organization in Jakarta but in Surabaya YKAKI is still not well-known among the people of Surabaya. Trust is important in the case of harsh diseases and therefore there must be a media that can explain the facilities in YKAKI clearly to generate trust in YKAKI. YKAKI itself is a Non-Profit organization which means that it does not benefit from their efforts but to protect and help hence a problem arises where YKAKI has to find sponsors in the form of funds large enough to cover the shortcomings of the many facilities to help children with cancer. Infographic is one form of beneficial promotion in providing information to people who do not know and can provoke curiosity and the disclosure of good and interesting information to be seen and read by people and therefore the use of infographic in the media of promotion and explanation of YKAKI facilities is very efficient and can attract many visitors and sponsors who want to help YKAKI Keywords: Child Cancer,facilities,YKAKI,Infographic,Sponsors,Visitors